2008
DOI: 10.1203/pdr.0b013e318184edeb
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors of Bronchopulmonary Dysplasia

Abstract: ABSTRACT:The aim of the study was to assess the association between bronchopulmonary dysplasia (BPD) and polymorphisms of genes coding for vascular endothelial growth factor (VEGF), transforming growth factor (TGF-␤1), insulin-like growth factor (IGF-1), and 5,10-methylenetetrahydrofolate reductase (MTHFR). A sample of 181 newborns with mean gestational age of 28 wk was prospectively evaluated. Molecular analysis of TGF-␤1 Ϫ800GϾA, Ϫ509CϾT, 10TϾC, 25GϾC, VEGF Ϫ460TϾC and 405GϾC and MTHFR 677CϾT polymorphisms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 29 publications
(31 reference statements)
1
29
3
1
Order By: Relevance
“…Interestingly, a recent report showed that a promoter polymorphism (Ϫ460 T/C) of the VEGF gene was associated with an increased risk of BPD, independently from the duration of O 2 exposure (12). Given the fact that MIF has been shown to promote angiogenesis (19,20) and to induce VEGF production in the neonatal mouse lung (23), and that both genes are HIF-inducible, it is tempting to speculate that polymorphisms of the MIF and VEGF genes may affect the same maturational pathway in neonatal lung.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report showed that a promoter polymorphism (Ϫ460 T/C) of the VEGF gene was associated with an increased risk of BPD, independently from the duration of O 2 exposure (12). Given the fact that MIF has been shown to promote angiogenesis (19,20) and to induce VEGF production in the neonatal mouse lung (23), and that both genes are HIF-inducible, it is tempting to speculate that polymorphisms of the MIF and VEGF genes may affect the same maturational pathway in neonatal lung.…”
Section: Discussionmentioning
confidence: 99%
“…The human lung undergoes maturation during five stages, each of which has distinct growth milestones at specific gestational periods [9]. The latter two stages extend from 26-28 to 32-36 weeks gestation [7,[12][13][14][15].…”
Section: Dysplasiamentioning
confidence: 99%
“…A recent animal study demonstrated that hypoxia had a substantial effect on LPS-induced pulmonary inflammation by increasing the magnitude of lung injury reflected by increased expression of inflammatory mediators, excessive neutrophil accumulation and increased vascular permeability [40] . The role of a genetic predisposition to BPD is currently under investigation but has not provided conclusive data to date [41][42][43] .…”
Section: Hyperoxia and Hypoxiamentioning
confidence: 99%